Optimización del proceso productivo de la línea de lácteos en la planta de procesamientos de agroindustrias de la Unidad Académica Caren de la Universidad Técnica de Cotopaxi periodo 2016 - 2017 - Pullupaxi Pujos, William Román (2017)
This research project has the objective of carrying out a technical study and implementation of a machine for the optimization of the dairy production process. In addition, these machines present operational problems, risks in processes of machinery distribution and machinery of production. Through a survey process of information and timing activities, we detected that all activities needed a large amount of time. These actions, processes, and procedures are not carried out by means of safe and adequate parameters for the good performance of workers that’s why their productivity is inefficient. As a result of simplification of work through engineering method, systematic planning, technological innovation, and logical ordering of processes costs are reduced and productivity has increased. The invested resources that are used at a given level of optimization set the costs of the production, so it turns out that when productivity grows the costs decreases by giving a total focus on product quality. The initial situation that we have studied gave us all of the knowledge that we already mention. …